Enzymatic transformation of flavonoids and terpenoids: Structural and functional diversity of the novel derivatives - Xanthakis, E.; Theodosiou, E.; Magkouta, S.; Stamatis, H.; Loutrari, H.; Roussos, C.; Kolisis, F. (2010)
Flavonoids and terpenoids are promising candidates for use as functional foods and novel therapeutics due to their prominent biological activities. However, the use of several bioactive plant compounds is limited by low stability and solubility problems. This review underlines the feasibility of enzymatic synthesis of novel bioactive analogs of selected flavonoids (silybin, rutin) and terpenoids (perillyl alcohol, POH) in nonconventional reaction systems. The effect of various parameters on the enzymatic acylation and/or glucosylation of these phytochemicals was studied. Also, the role of the structure of the novel Molecules in relation to their biological function was investigated in various cancer cell lines. Pure and Applied Chemistry